Transborder Insecurity in the Sahel: Assessing Non-state Actors in Enabling Terrorism in Mali - Check, Nicasius Achu; Diarra, Issiaka (Scientia Militaria - South African Journal of Military Studies, 2023)
The paper seeks to examine the role of non-state actors in enabling terrorism and insecurity in Mali. It analyses the insecurity situation in Mali within the broader challenge of insecurity and religious conflict in West Africa. The paper argues that the lack of political will by the various post-colonial governments to address the concerns of the Tuaregs may have contributed to the security challenges the country faces soon after the collapse of the Muammar Ghaddafi administration in Libya. The paper contends that transhumanism as a migratory pattern and the porosity of international boundaries along the Sahel region are enabling variables for the country's insecurity and instability. Though how transhumanism is practised today may have changed, the methodological approach in which it is carried out has not. However, many have argued that the root causes of terrorist acts and violent conflict in post-independence Africa are not the unmet promises to address poverty and unemployment but people's experiences of inequality and relative deprivation. In other words, people are dissatisfied when comparing their quality of life and economic and social opportunities with those of better-off countries and communities. The paper attempts to clarify some of the critical theoretical issues political elites need to look out for as they put measures to address fundamental challenges the country is facing. The concept of the 'ungoverned Spaces' was elaborated upon and insisted that the vast uninhabited spaces in Mali are breeding groups for terrorists with their nebulous activities. The paper concludes by suggesting that the government should renegotiate a social compact with the people of Mali and start re-engineering a kind of rapprochement between the people and the government.